The intelligibility of Polish speech synthesized with a new SineWave Synthesis method - GARDZIELEWSKA, Hanna; PREIS, Anna (Archives of Acoustics, 2007)
SineWave Synthesis, (SWS), allows a significant reduction of the information carried by a speech signal representing by the dynamic spectral properties of formants selected from the natural speech. The synthesis rejects all the detailed acoustic information carried by a signal, including the fundamental frequency as well as harmonic and noise components. Regardless of the impressive information reduction (the compression coefficient for 3-tone synthesis reaches even 195:1), the linguistic and extra-linguistic information of a signal are to a large extend preserved. For the first time, a modified version of SWS was used to analyze Polish speech in order to evaluate the relationship between data reduction and the intelligibility of speech. Speech intelligibility was tested in different utterances varying in grammatical structure, linguistic information, and duration. The modified SWS method, elaborated in Adam Mickiewicz University in Poznań, provided noticeably better results for Polish speech than the original method elaborated in late 1970s at Haskins Laboratories.